The Oxford Handbook of Language Attrition 2019
DOI: 10.1093/oxfordhb/9780198793595.013.22
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Extralinguistic Factors in Language Attrition

Abstract: One of the most puzzling explanatory challenges to language attrition research is to identify the circumstances and predictors under which any particular speaker is likely to experience more or less attrition phenomena: it is a well-established finding that speakers who use more than one language in their daily lives develop increased variability concerning their first language (L1) skills across the full range of the linguistic repertoire, from phonetics through the lexicon and morphosyntax to pragmatics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It is possible that their perception and production have become more lenient toward Korean than native English speakers who never left their home countries. There is ample evidence that experience with an L2 can affect many features of the L1 at both segmental and suprasegmental levels (for a review, see Schmid and Köpke, 2019). Chang (2012), for example, found that even with brief experience in L2 (the first weeks of elementary Korean studies), English learners of Korean produced the VOT of their L1 voiceless stops as drifted toward the longer VOT norms of a similar L2 stop (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that their perception and production have become more lenient toward Korean than native English speakers who never left their home countries. There is ample evidence that experience with an L2 can affect many features of the L1 at both segmental and suprasegmental levels (for a review, see Schmid and Köpke, 2019). Chang (2012), for example, found that even with brief experience in L2 (the first weeks of elementary Korean studies), English learners of Korean produced the VOT of their L1 voiceless stops as drifted toward the longer VOT norms of a similar L2 stop (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the nature of this process requires looking in more detail at the predictors of language attrition. However, as pointed out by Schmid and Cherciov (2019), attrition studies face the methodological challenge of reduced population size, high variability of the collected data and an enormous difficulty in quantifying extralinguistic variables. This also applies to studies on returnee bilinguals, whose population is even more reduced than the populations who live in the migration context.…”
Section: Predictive Variables In Language Attrition and Research Ques...mentioning
confidence: 99%
“…Even more than a common theoretical framework, attrition research requires a methodological boost. The Oxford Handbook of Language Attrition ( Schmid et al, 2019 ) recently dedicated several chapters to neuroimaging approaches ( Rossi et al, 2019 ; Steinhauer and Kasparian, 2019 ). While providing a thorough overview of existing studies in the field, these chapters reiterate the need for more research that would provide better conceptualization of this phenomenon.…”
Section: Building a Framework: In Search Of The Neural Correlates Of Attritionmentioning
confidence: 99%